2020
DOI: 10.3389/fbioe.2020.580090
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Long-Term Analysis of Lactic Acid and Ammonium Production in Non-growing Lactococcus lactis Reveals Pre-culture and Strain Dependence

Abstract: In various (industrial) conditions, cells are in a non-growing but metabolically active state in which de novo protein synthesis capacity is limited. The production of a metabolite by such non-growing cells is dependent on the cellular condition and enzyme activities, such as the amount, stability, and degradation of the enzyme(s). For industrial fermentations in which the metabolites of interest are mainly formed after cells enter the stationary phase, the investigation of prolonged met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Taken together these experiments show that manganese-mediated acceleration of acidification correlates with a disruption of redox homeostasis rather than energy homeostasis (ATP/ADP), leading to depletion of NADH and thereby stagnating acidification and possibly inducing a VBNC state. This loss of redox homeostasis is not seen in absence of manganese where NADH pools are apparently kept constant and acidification can be sustained for weeks (27) in these TB-cell suspensions. The copyright holder for this this version posted December 15, 2021. ; https://doi.org/10.1101/2021.12.14.472734 doi: bioRxiv preprint when starting the reaction after 0h (blue) and 20h (red) of incubation with TB.…”
Section: Manganese Leads To Nadh Depletion In Acidifying Tb-cellsmentioning
confidence: 86%
See 1 more Smart Citation
“…Taken together these experiments show that manganese-mediated acceleration of acidification correlates with a disruption of redox homeostasis rather than energy homeostasis (ATP/ADP), leading to depletion of NADH and thereby stagnating acidification and possibly inducing a VBNC state. This loss of redox homeostasis is not seen in absence of manganese where NADH pools are apparently kept constant and acidification can be sustained for weeks (27) in these TB-cell suspensions. The copyright holder for this this version posted December 15, 2021. ; https://doi.org/10.1101/2021.12.14.472734 doi: bioRxiv preprint when starting the reaction after 0h (blue) and 20h (red) of incubation with TB.…”
Section: Manganese Leads To Nadh Depletion In Acidifying Tb-cellsmentioning
confidence: 86%
“…Long term analysis of metabolite production was performed as described earlier (27). Exponentially growing cells pre-cultured in the presence or absence of Mn were harvested and resuspended at a density between 1E+07 and 2.5E+07 cells/mL in their corresponding growth medium supplemented with erythromycin (5µg/mL) and 10µM 5(6)-carboxyfluorescein (Sigma-Aldrich 21877), with or without Mn (20µM).…”
Section: Acidification and Luminescence Measurements Of Tb-cellsmentioning
confidence: 99%
“…The Lb. plantarum strains are described in (Molenaar et al, 2005;Smits et al, 2005;Siezen et al, 2010). Skimmed milk (Tritium Microbiologie) from the same batch was used for all growth experiments.…”
Section: Strains and Mediamentioning
confidence: 99%
“…Acidification can be monitored either directly with pH probes or indirectly through the use of fluorescent pHsensitive dyes. The dyes allow acidification tracking of many cultures in parallel using multiwell plates (John et al, 2003;Wegkamp and Reemst, 2018;Nugroho et al, 2020). Acidification is a function of the cell density and biomass specific acidification rate.…”
Section: Introductionmentioning
confidence: 99%
“…The evolved strains grew slower and reached higher culture densities driven by mutations that led to reduced rates of glucose import and glycolytic flux, which elicited a switch from homolactic to mixed acid fermentation leading to increased metabolic efficiency and biomass yield (Bachmann et al 2013;Bachmann et al 2017). In addition, a recent study revealed that these biomass-yield optimised strains also had an activated arginine utilisation pathway, further enhancing their metabolic capacity for energy generation to support biomass formation (Nugroho, Kleerebezem and Bachmann 2020). Notably, the reduced growth rate, increased biomass yield and acetic acid production resemble the physiological characteristics of ldh mutants of L. lactis, further supporting the pivotal role of lactic acid production by LDH in maintenance of the redox balance required to sustain high glycolytic flux and maximal growth (and acidification) rate.…”
Section: Pyruvate Dissipation Controlmentioning
confidence: 99%